Impact of cancer mutational signatures on transcription factor motifs in the human genome - Chan, Calvin Wing Yiu; Gu, Zuguang; Bieg, Matthias; Eils, Roland; Herrmann, Carl (BMC medical genomics, 2019)
Somatic mutations in cancer genomes occur through a variety of molecular mechanisms, which contribute to different mutational patterns. To summarize these, mutational signatures have been defined using a large number of cancer genomes, and related to distinct mutagenic processes. Each cancer genome can be compared to this reference dataset and its exposure to one or the other signature be determined. Given the very different mutational patterns of these signatures, we anticipate that they will have distinct impact on genomic elements, in particular motifs for transcription factor binding sites (TFBS).